Предмет: Алгебра,
автор: hitli899
(2y-3)²+(y-3)(y+3)+12y при у=-2 равно 20 помогите срочнооо!!!
Ответы
Автор ответа:
1
Замінюємо вираз у=-2:
(2y-3)² + (y-3)(y+3) + 12y = (2*(-2)-3)² + (-2-3)(-2+3) + 12*(-2)
= (-7)² + (-5) + (-24)
= 49 - 5 - 24
= 20
Отже, при у = -2, значення виразу дорівнює 20.
(2y-3)² + (y-3)(y+3) + 12y = (2*(-2)-3)² + (-2-3)(-2+3) + 12*(-2)
= (-7)² + (-5) + (-24)
= 49 - 5 - 24
= 20
Отже, при у = -2, значення виразу дорівнює 20.
hitli899:
спасибо
Похожие вопросы
Предмет: Литература,
автор: temirlantulebaev80
Предмет: Английский язык,
автор: kinalmaksim9
Предмет: История,
автор: milakamila201125
Предмет: Физика,
автор: uijyu7gbbccb
Предмет: Математика,
автор: goldaserya